KOMUNITAS MASYARAKAT PESISIR DI TAMBAK LOROK, SEMARANG - Fama, Achmad (Sabda: Jurnal Kajian Kebudayaan, 2016)
Tambak Lorok is a coastal area located near the Tanjung Mas Harbour, where many residents work as fishermen. These residents living in Tambak Lorok are mostly using the traditional way to work on a fishing operation. They use a simple utility to catch fish. This paper mainly discusses about the structure of the community citizens of Tambak Lorok. Since they live near the offshore, oftenly they are called as a coastal community. Â As citizens which depend so much on the sea to fulfill their needs, many hunt fish. The description on this local society can be divided on the basis of their occupation, gender, social, and economy